Aadil Aliyin Kaalanigal ஆதில் அலியின் காலணிகள் - Gilani-Williams, Fawzia,Wadia, Niloufer,Pālēntirā, Pūraṇi (Tulika Publishers, 2018)
The story of Adil Ali and his old shoes.
Children's story. - Translated from English. - Translation of: Adil Ali's shoes
Keywords: Shoes; Juvenile fiction; Pictorial works.; Children's stories; Indic (English); Translations into Tamil.; Children's stories; Indic (English); Translations into Tamil; Pictorial works.